2004
DOI: 10.1088/0022-3727/37/20/001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an ac magnetic field and induced magnetic anisotropy on the surface magnetoimpedance tensor in an amorphous wire

Abstract: The influence of an ac magnetic field and the induced magnetic anisotropy (by field annealing and torsion annealing) on the magnetoimpedance (MI) tensor in an amorphous wire has been analysed. The experimental measurements were carried out in an amorphous wire of composition (Co0.94Fe0.06)72.5Si12.5B15, with a negative, nearly zero magnetostriction constant, excited either by an ac circular, hϕ, or an axial, hz, magnetic field created by an ac electric current passing along the wire or through an exciting coil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Considerable attention have been given to describe the MI effect in samples presenting cylindrical geometry with distinct anisotropy configurations [44][45][46][47] . For this case, e. g., Makhnovskiy et al 45 have reported a very strict study on the surface impedance tensor, in which theoretical results for the cylindrical geometry are directly compared to experimental measurements acquired for ferromagnetic wires.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable attention have been given to describe the MI effect in samples presenting cylindrical geometry with distinct anisotropy configurations [44][45][46][47] . For this case, e. g., Makhnovskiy et al 45 have reported a very strict study on the surface impedance tensor, in which theoretical results for the cylindrical geometry are directly compared to experimental measurements acquired for ferromagnetic wires.…”
Section: Introductionmentioning
confidence: 99%
“…Under the same conditions the ends of the wire sample were clamped to allow a simultaneous application of a torsion stress of π/4 rad cm −1 . This treatment modifies the circularly magnetized sheath of the sample, developing a helically magnetized surface layer [18][19][20]. Although this helical anisotropy is not uniform along the wire radius, we can consider it roughly uniform at high enough frequencies because in this case the current flows in a thin surface layer.…”
Section: Experimental Measurementsmentioning
confidence: 99%
“…This induced anisotropy obviously affects the GMI response. Also, quite recently, we have reported in [20] experimental results on the effect of the helical anisotropy on the GMI effect. Such anisotropy was induced by a torsion annealing treatment.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since the system geometry has an important role on MI results, several studies have been performed to obtain further information on this dependence. Considerable attention have been given to describe the MI effect in samples presenting cylindrical geometry with distinct anisotropy configurations [44][45][46][47] . For this case, e. g., Makhnovskiy et al 45 have reported a very strict study on the surface impedance tensor, in which theoretical results for the cylindrical geometry are directly compared to experimental measurements acquired for ferromagnetic wires.…”
Section: Introductionmentioning
confidence: 99%